Remittance and economic growth nexus in Nigeria: Does financial sector development play a critical role? - Friday Osemenshan Anetor (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The purpose of the study was to examine the relationship between remittances, financial sector development, and economic growth in Nigeria over the period 1981 to 2017. The study used the autoregressive distributed lag (ARDL) model to analyze the long-run and short-run relationships between the variables. The outcome of the study revealed that the variables are bound together in the long-run. The results also showed that remittances have a negative and significant effect on economic growth both in the long-run and short-run. The study also established that financial sector development has a negative and significant impact on economic growth both in the long-run and short-run. Further, the study confirmed the existence of complementarity between remittances and financial sector development in influencing economic growth. In addition, study revealed that inflation has a negative and significant effect on economic growth both in the long-run and short-run. The findings of the study showed that trade openness, government expenditure, and population growth have no significant impact on economic growth both in the long-run and short-run.
Keywords: F24; F43; O16; 330; Remittances; financial development; economic growth; ARDL; Nigeria